نظرة الى اساليب بيان النص الشرعي : بحث في علوم أدلة التشرع المتعارضة في الفكر الإسلامي (دراسة تحليلية) (Nazrat ila asalib bayan al-nas al-shar'i : bahth fi 'ulum adillat al-tashri' al-muta'aridah fi al-fikr al-Islami (dirasah tahliliyah)) - Ahmed Shogar, Ibrahim Adam (IIUM Press, 2011)
The entire Islamic teachings are based on Divine revelation, i.e. the Holy Qur`an and Sunnah of the Prophet (S). The Islamic legal rules are generally inferred from the Qur`an and Sunnah, therefore, the proper understanding of these two sources is the main objective of all Muslim scholars. The style of the Qur`anic passages, as Divine word, is very high, hence deducting the meaning from the Qur`anic verses can be in various ways. This fact has produced conflicting ideas in Islamic thought and created what known in Islamic jurisprudence as “Sciences of Conflict and Reconciliation of Proofs”. This book discusses the basic principles and historical development of this science. The study approaches the topic from two basic dimensions: First, it analyzes the concept of conflict and reconciliation of proofs and investigates its historical roots. The second dimension focuses on the actual factors that behind the conflict of proofs and presents the most important works of Islamic thought on the matter. The entire subject of the book is constructed on five chapters, including the introductory chapter: the first chapter is about meaning and different types of conflict of legal rules. The second chapter focuses on the basic concepts. The third chapter reflects the historical background of conflict of proofs in Islamic thought. The final chapter elaborates on the different approach of reconciliation. The main objective of the book is to draw attention of modern Muslim scholars and scientists to our intellectual legacy and its role for better understanding of the Qur`an and Sunnah.